2015
DOI: 10.1111/1365-2435.12422
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between transgenerational transfer of nutritional stress tolerance and immune priming

Abstract: Summary1. Transgenerational effects are often assumed to have adaptive value as a driver of variation in offspring and parental fitness. Studies of transgenerational effects often focus on single environmental variables. However, in nature, it is unlikely for one factor to vary independently from others and there are likely to be trade-offs between different stressors. 2. We altered the nutritional environment of both parents and offspring to examine how nutritional stress influences transgenerational immune p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 48 publications
0
32
2
Order By: Relevance
“…Thus, the use of two different classes of bacteria may have elicited a stronger response. Furthermore, while haemolymph immunity can play a role in insect resistance to Bt (Dubovskiy et al, 2008;Grizanova et al, 2014;Shikano et al, 2015), the concentration-dependent change in Bt-resistance of Pseudomonas-fed T. ni found here may have resulted from an altered composition of the midgut bacterial community. Direct antagonism of Bt by midgut bacteria, as observed in other lepidopteran larvae (Johnston & Crickmore, 2009;Raymond et al, 2010), might contribute to heightened resistance at low concentrations, whereas opportunistic invasion of the haemocoel by Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Thus, the use of two different classes of bacteria may have elicited a stronger response. Furthermore, while haemolymph immunity can play a role in insect resistance to Bt (Dubovskiy et al, 2008;Grizanova et al, 2014;Shikano et al, 2015), the concentration-dependent change in Bt-resistance of Pseudomonas-fed T. ni found here may have resulted from an altered composition of the midgut bacterial community. Direct antagonism of Bt by midgut bacteria, as observed in other lepidopteran larvae (Johnston & Crickmore, 2009;Raymond et al, 2010), might contribute to heightened resistance at low concentrations, whereas opportunistic invasion of the haemocoel by Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 80%
“…Regardless of the mechanisms, slower growth from consuming non-entomopathogenic bacteria can be detrimental as it prolongs the exposure of the most vulnerable younger stages to pathogens and other natural enemies. Reduced food quality and the abundance of midgut bacteria are also associated with higher larval susceptibility to baculoviruses (Jakubowska et al, 2013;Shikano et al, 2015), and may have contributed to the slightly faster mortality of Pseudomonas-fed T. ni after virus challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Egg provisioning or neonate size can relate to fitness of insects in terms of individual quality/vigour (Wellington, 1960) or to overwintering survival of embryonic larvae within eggs (Harvey, 1985;Fitzpatrick & Troubridge, 1993;Fischer et al, 2003). In addition, a recent study has also shown increased egg size of cabbage looper, T. ni, after larvae were exposed to a sub-lethal concentration of the bacterial pathogen Bacillus thuringiensis (Shikano et al, 2015a). We predicted that egg size would increase for females fed induced foliage or foliar bacteria, if these acted as stressors that initiated higher investment in offspring quality versus quantity.…”
Section: Egg Size and Qualitymentioning
confidence: 99%